Analysis of Water and Hydroxyl Species in Soda Lime Glass Surfaces Using Attenuated Total Reflection (ATR)‐IR Spectroscopy. Issue 1 (6th October 2015) - Amma, Shin‐ichi; Kim, Seong H.; Pantano, Carlo G.
Abstract : ATR‐IR spectroscopy is a useful and convenient method for evaluation of local structure and concentration of water and hydroxyl species in glass because it can be more surface sensitive than reflection or transmission IR analysis. In this work, a semiquantitative analysis of the ATR spectra of OH groups and interstitial molecular water species in glass surfaces after various surface treatments is presented. Both hydroxyl groups and interstitial molecular water exist in the hydrated surfaces but the relative water speciation varies with surface treatment. The SiOH and H2 O species in the glass surface showed a wide range of hydrogen bonding interactions and their distributions varied with the SO2, polishing, acid leaching, thermal tempering, and chemical strengthening treatments. SIMS analysis of the hydrogen concentration — depth profiles for the acid‐leached samples was used to provide independent information to validate and quantify the ATR signal.